Evaluation of skin response after erbium:yttrium–aluminum–garnet laser irradiation: a network analysis approach - Rezaei-tavirani, Majid; Rezaei Tavirani, Mostafa; Zamanian Azodi, Mona; Razzaghi, Mohammadreza; Moravvej Farshi, Hamideh (Journal of Lasers in Medical Sciences, 2019)
Introduction: Application of laser in medicine and cosmetic purposes has raised grossly in recent years. There are contradictory finding about its side effects. In this research critical differentially expressed proteins after irradiation erbium:yttrium–aluminum–garnet (Er:YAG) laser on skin are investigated. Methods: Proteome data including 31 proteins were obtained from a proteomics investigation of laser irradiation, Er:YAG on female mouse skin that are published by Pan et al. The query proteins and 100 related ones were included in the protein-protein interaction (PPI) network. The central nodes were determined and all of nodes were included in action maps. Expression, activation, inhibition, binding, and reaction were considered in action plan. Results: Numbers of 16 proteins were recognized by STRING database and were included in the network. Except PHRF1, the other 15 query proteins were included in the main connected component of the constructed network. Ten central nodes of the network and ten numbers of top query proteins based on degree value were identified as central proteins of the network. All nodes of the network analyzed via action maps and the important acted nodes were determined as RPSA, GAPDH, TPT1, DCTN2, HSPB1, and PDIA3. Conclusion: Two balanced processes including cancer promotion and cancer prevention were after irradiation were identified.